Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

I am reading a passage of text that states:

"We can use the fact that $e^{a+bi}=e^a(\cos b+i\sin b)$ has polar form $\left<e^a,b \right>$ to verify that complex exponentials have various properties that we would expect, by analogy with real exponentials."

It then goes on to ask to express $e^z \times e^w$ in polar form where $z=a+bi$ and $w=c+di$.

Using the rule presented in the text above I can do this, what I am not clear on however is why this statement is true:

"We can use the fact that $e^{a+bi}=e^a(\cos b+i\sin b)$ has polar form $\left<e^a,b \right>$".

I expect I am overlooking something here but I am not making much progress. I am not sure how the polar form in this general case has been derived.

share|improve this question
add comment

3 Answers

up vote 3 down vote accepted

Let's do it piece by piece. In general, we know that the following is a property of the exponential function:

$$ e^{x + y} = e^x \cdot e^y $$

Replace $x$ with $a$ and $y$ with $b\,i$ to get:

$$ e^{a + b i} = e^a \cdot e^{b i} $$

Now for $e^{b\,i}$, use Euler's formula which states that:

$$ e^{b i} = \cos b + i\sin b $$

Apply this formula to get the result:

$$ e^{a + b i} = e^a (\cos b + i\sin b) $$

share|improve this answer
add comment

For all $z\in\mathbb{C}$, we define:

$$ e^{z}=1+z+\frac{z^2}{2!}+...=\sum_{n=0}^{\infty}\frac{z^n}{n!} $$

Notice, that if we replace complex $z$ in real $x$, we'll get the expansion of the real value function $e^x$.

We prove that for all $z\in\mathbb{C}$ and $x\in\mathbb{R}$,

$$e^x\cdot e^z=e^{x+z}$$

By the above definition, we get: $e^x=\sum_{n=0}^{\infty}\frac{x^n}{n!}$ and $e^z=\sum_{n=0}^{\infty}\frac{z^n}{n!}$. The series are converges absolutely, and therefor we can multiply them:

$$e^x\cdot e^z=1+(x+z)+(\frac{x^2}{2!}+xz+\frac{z^2}{2!})+...+(\frac{x^n}{n!}+\frac{x^{n-1}}{(n-1)!}z+...+\frac{z^n}{n!})+...=$$

$$=1+(x+z)+\frac{1}{2!}(x+z)^2+...+\frac{1}{n!}(x+z)^n+...=e^{x+z}$$


Now, let say that $x=a$ and $z=ib$, applying Euler's formula, we'll get out wanted result.

share|improve this answer
add comment

By a polar form, $z=\rho e^{i\theta}$, for a complex number it is intedend the couple of the modulus $\rho$ and the phase $\theta$. So, $z=\langle \rho,\theta\rangle$. In your case is $\rho=e^a$ and $\theta=b$.

share|improve this answer
add comment

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.